Pengembangan Game Edukasi Gerabah-Rush sebagai Game Unggulan Industri Gerabah Pagelaran - Iriaji; Ike Ratnawati; Abdul Rahman Prasetyo; Alby Aruna; Eka Putri Surya; Adinda Marcelliantika; Ginanjar Atma Wijaya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This community service program aims to develop the educational game "Gerabah-Rush" as a flagship game for the pottery industry in Pagelaran Village. The methodology includes educational and promotional needs analysis, game content design, and evaluation of the game's effectiveness in increasing youth interest and engagement with pottery crafts. The game is designed to provide an interactive and immersive experience about the pottery-making process, history, and cultural values embedded within it. Program results show a significant increase in young people's interest and awareness of local pottery crafts. Evaluations through surveys and in-depth interviews confirm that this educational game is effective in promoting pottery crafts and enhancing their educational value. This program makes a significant contribution to modernizing educational and promotional assets for pottery crafts and ensuring the sustainability of the pottery industry in Pagelaran Village.